PENGEMBANGAN MEDIA HYPERMEDIA ENYAHKAN ASAP ROKOK SEBAGAI PENCEGAHAN DIABETES MELITUS PADA PENGELOLA PASAR - Gebriel Metondia Gurning; Iryanti (Politeknik Kesehatan Kemenkes Bandung, 2025)
Diabetes Mellitus (DM) is one of the leading non-communicable diseases with a high mortality rate in Indonesia. Smoking is a risk factor for DM that is often overlooked. Market managers have a high level of exposure to cigarette smoke and have not received adequate health education. This study aimed to Development hypermedia-based educational media on the dangers of smoking as a strategy for DM prevention among market managers. This research employed the 4D Development model (Define, Design, Development, Disseminate) conducted at Caringin Central Market. The define stage was carried out through semi-structured interviews with five informants using the snowball sampling technique. The design stage produced a draft of the educational media, including content structure, navigation, and layout. In the Development stage, an interactive hypermedia prototype was created in HTML5 format, incorporating illustrations, audio, and quizzes. The disseminate stage was conducted through digital distribution using WhatsApp to the target users. Validation tests were carried out by material experts, media experts, and end users (75 participants). Validation by material experts yielded a score of 98% and by media experts 94% (both categorized as highly feasible). User trials showed a score of 83% in the small group and 95% in the large group. Dissemination was conducted digitally via WhatsApp and documented with receipts. The “Enyahkan Asap Rokok” hypermedia was rated highly feasible, easily accessible, and well-accepted by users. Hypermedia proved to be effective as a health promotion strategy in improving knowledge and preventing DM through smoking reduction.